Some Clinical and Subclinical Characteristics of Patients with Castration-resistant Prostate Cancer in Huu Nghi Hospital - Thi Khanh Tam, Le; Cam Phuong, Pham; Phuong Hoa, Nguyen (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 39 No 1DO - 10.25073/2588-1132/vnumps.4433, 2023)
Abstract: This study aims to describe the clinical and subclinical characteristics of patients with castration-resistant prostate cancer (CRPC). The retrospective study was conducted on 46 patients with CRPC in Huu Nghi Hospital. The results indicated that the main clinical symptoms were bone pain (63.0%), hematuria (34.0%), and lower urinary tract symptoms (32.6%). The highest and lowest PSA concentrations were 611.3 ng/mL and 0.01 ng/mL, respectively. The most common sites of metastasis were bone (82.6%), lymph node (50.0%), and lung (19.6%). These patients were all at the late stage, so most of them had symptoms of metastasis and high PSA. Keywords : Prostate cancer, castration-resistant, clinical characteristics, subclinical characteristics.